2021
DOI: 10.31219/osf.io/3x7z8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Couples Therapy for a Divided America: Assessing the Effects of Reciprocal Group Reflection on Partisan Polarization

Abstract: Overcoming America’s deep partisan polarization poses a unique challenge: Americans must be able to disagree on policy while nonetheless agreeing on more fundamental democratic principles. We study one model of depolarization—reciprocal group reflection—inspired by marital counseling and implemented by a non-governmental organization, “Braver Angels.” We randomly assigned undergraduate students at four universities either to participate in a Braver Angels workshop or simply to complete three rounds of surveys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…As another example, Bilali and Vollhardt (2013) assessed the efficacy of Musekeweya (New Dawn), a Rwandan radio drama developed by the NGO Radio La Benevolencija that aims to prevent violence and promote reconciliation following genocide. Just like Bruneau et al (2021), these researchers evaluated the efficacy of the radio program following development and deployment and found that it improved intergroup relations through a variety of psychological processes (e.g., perspective-taking, Bilali & Vollhardt, 2013; see also Baron et al, 2021; Bilali et al, 2016; Paluck, 2009; Paluck & Green, 2009; Staub, 2019). In these examples, the authors investigated whether already existing intervention programs developed by practitioners resulted in improved intergroup relationships.…”
Section: Spectrum Of Ways To Conduct Translational Sciencementioning
confidence: 99%
“…As another example, Bilali and Vollhardt (2013) assessed the efficacy of Musekeweya (New Dawn), a Rwandan radio drama developed by the NGO Radio La Benevolencija that aims to prevent violence and promote reconciliation following genocide. Just like Bruneau et al (2021), these researchers evaluated the efficacy of the radio program following development and deployment and found that it improved intergroup relations through a variety of psychological processes (e.g., perspective-taking, Bilali & Vollhardt, 2013; see also Baron et al, 2021; Bilali et al, 2016; Paluck, 2009; Paluck & Green, 2009; Staub, 2019). In these examples, the authors investigated whether already existing intervention programs developed by practitioners resulted in improved intergroup relationships.…”
Section: Spectrum Of Ways To Conduct Translational Sciencementioning
confidence: 99%
“…While many Americans avoid political discussion, they are still more likely to share political opinions with friends and family (Cowan and Baldassarri 2018). Organizations such as Braver Angels can help provide resources for those interested in navigating these challenging conversations (Baron et al 2021). However, the results of these depolarization efforts may not properly account for the additional political conflict that marginalized groups experience.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesizing some of the classic work on contact theory with recent insights from depolarization interventions, we propose two additional conditions that may lead to greater success in the political context. In addition to the four conditions outlined above, it also may be beneficial to 5) include training in dialogue skills [18,[113][114][115], and 6) structure contact interventions to highlight commonalities [29].…”
Section: Intervening On Relationshipsmentioning
confidence: 99%
“…The discussions focus on policy issues, but also encourage specific forms of dialogue between partisans while highlighting the things they share in common, such as their agreement on many key policy issues [97]. Their work reduces animosity and even increases monetary support for depolarization initiatives [113].…”
Section: Fostering Positive Contactmentioning
confidence: 99%